Aktivitas Antioksidan dan Nilai SPF (Sun Protection Factor) Ekstrak Etanol Buah Pepaya (Carica papaya L.) yang Diperoleh dari Simplisia dan Buah Segar - Aditya Noviadi Rakhmatullah; Nining Sugihartini; Hari Susanti (Jurnal Surya Medika (JSM), 2020)
Papaya contains vitamin C and beta-carotene which are useful as antioxidants and can be used as a sunscreen. The content of the active substance is affected by the type of raw material. This study aims to determine the antioxidant activity and SPF value of extracts obtained from simplicia and fresh fruit. Extracts obtained from simplicia and fresh fruit were determined antioxidant activity by DPPH method and SPF values by spectrophotometric method. The results showed that the antioxidant activity of papaya extract obtained from simplicia had IC50 values smaller than papaya extract obtained from fresh fruit, whereas the papaya extract obtained from simplicia had IC50 values of 175 μg / mL and the papaya extract obtained from fruit fresh is 209 μg / mL. While in the sunscreen test, the SPF value of papaya extract obtained from simplicia is greater than the papaya extract obtained from fresh fruit. SPF value of papaya extract obtained from simplicia is 37, while papaya extract obtained from fresh fruit is 35. The conclusion from this study is papaya extract extracted by the drying process of the initial material (simplicia) has antioxidant activity and SPF values that are more optimal than papaya extracts extracted without going through a drying process first (fresh fruit).